The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1118/1.1688212
|View full text |Cite
|
Sign up to set email alerts
|

Performance of electronic portal imaging devices (EPIDs) used in radiotherapy: Image quality and dose measurements

Abstract: The aim of our study was to compare the image and dosimetric quality of two different imaging systems. The first one is a fluoroscopic electronic portal imaging device (first generation), while the second is based on an amorphous silicon flat-panel array (second generation). The parameters describing image quality include spatial resolution [modulation transfer function (MTF)], noise [noise power spectrum (NPS)], and signal-to-noise transfer [detective quantum efficiency (DQE)]. The dosimetric measurements wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
40
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 42 publications
3
40
2
Order By: Relevance
“…Megavoltage (MV) electronic portal imaging device (EPID) has been widely used as an on‐line verification tool for treatment field in radiation therapy 1, 2, 3, 4. While the weight of the verification tool appears to be decreased after the emergence of kilovoltage (kV) imager mounted on a linear accelerator, EPID images still have their own advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Megavoltage (MV) electronic portal imaging device (EPID) has been widely used as an on‐line verification tool for treatment field in radiation therapy 1, 2, 3, 4. While the weight of the verification tool appears to be decreased after the emergence of kilovoltage (kV) imager mounted on a linear accelerator, EPID images still have their own advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have investigated the use of electronic portal imaging devices for quality assurance purposes such as MLC position verification (16)(17)(18) and IMRT patient specific dose verification (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Renner et al (24) reported on four different methods that have been introduced for the purpose of using the EPID for treatment verification: 1) Compute the dose from each beam to the EPID and compare to the actual EPID image of each beam (4-15); 2) Use the EPID to verify the leaf positions for intensity modulated fields (16)(17)(18); 3) Reconstruct the dose to the patient using the exit image acquired during treatment (20)(21)(22)(23); and 4) Convert the EPID images to an incident fluence distribution and use it for dose calculation employing the patient CT anatomy (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Such alternative techniques are electronic portal imaging devices [1,3,5,7,11,20,23,35] or the digital luminescence radiography [2,4,13,16,17,32,37].…”
Section: Introductionmentioning
confidence: 99%